Antecedents of Sustainable SMEs in the Social Media Space: A Partial Least Square-Structural Equation Modeling (PLS-SEM) Approach - Amoah John; Belás Jaroslav; Khan Khurram Ajaz; Metzker Zdenko (Management şi Marketing, 2021)
Social media has become explosive, permeating every sphere of the socio-cultural lives of individuals and businesses, and causing nations to technologically evolve. The dramatic growth in the adoption and use of social media has become beneficial to Small and Medium Enterprises (SMEs), significantly contributing to resolving a nagging challenge of effectively advertising their goods and services. Consequently, SMEs can achieve business growth and sustainability through increased adoption and harnessing the opportunities provided through the use of social media. The COVID-19 pandemic has provided an impetus for both consumers and SME businesses to leverage interaction through social media, which may lead to business growth. This research thus sets out to identify how social media contributes to the growth of SMEs within a developing country context. To accomplish this objective, primary data was collected from SMEs in the hospitality industry across the sixteen administrative regions of Ghana using survey and simple random sampling techniques. Questionnaires were distributed to the managerial staff of each randomly selected survey participant. Out of the 900 questionnaires distributed, 718 were filled correctly for the data analysis. The researchers quantitatively analyzed the responses using Partial Least Square-Structural Equation Modeling(PLSSEM) statistical software ADANCO 2.0 version. The results indicated that Small and Medium Enterprises are capable of using social media for customer attraction, business marketing strategy, communication channel and increased financial performance.